2018
DOI: 10.1007/s00402-018-3021-y
|View full text |Cite
|
Sign up to set email alerts
|

The value of radiography in the follow-up of extremity fractures: a systematic review

Abstract: BackgroundThe added value of routine radiography in the follow-up of extremity fractures is unclear. The aim of this systematic review was to create an overview of radiography use in extremity fracture care and the consequences of these radiographs for the treatment of patients with these fractures.Materials and methodsStudies were included if they reported on the use of radiography in the follow-up of extremity fractures and on its influence on treatment strategy, clinical outcome, or complications. A compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
(41 reference statements)
2
15
0
Order By: Relevance
“…Literature on the (cost-)effectiveness of omitting routine extremity radiography is scarce. This is discussed in our retrospective review [ 37 ] and has been confirmed by researchers investigating the usefulness of an additional shoulder radiograph [ 38 ]. Results from this study however were consistent with results from our study which examined the cost-effectiveness of reduced imaging in distal radius fractures [ 39 ].…”
Section: Discussionsupporting
confidence: 71%
“…Literature on the (cost-)effectiveness of omitting routine extremity radiography is scarce. This is discussed in our retrospective review [ 37 ] and has been confirmed by researchers investigating the usefulness of an additional shoulder radiograph [ 38 ]. Results from this study however were consistent with results from our study which examined the cost-effectiveness of reduced imaging in distal radius fractures [ 39 ].…”
Section: Discussionsupporting
confidence: 71%
“…However, there is growing evidence that this is of limited value. [29] This further raises the question if today, in contrast to routine care, rapid-access patient-initiated follow-up, imaging and/or physiotherapy might not better suit patient's needs, at reduced healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review by van Gerven et al . concluded that some, if not all, post‐operative imaging of extremity fractures can be eliminated without significant impacts on patient outcomes, management or the development of a treatment strategy 19 . However, it is important to note that both of these systematic reviews by Teo et al 11 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that both of these systematic reviews by Teo et al 11 . and by van Gerven et al 19 . have been limited by the heterogenous nature of the literature and patient demographics analysed in this field.…”
Section: Discussionmentioning
confidence: 99%